Early crack orientation prediction methods under fretting fatigue loading including wear effects. (August 2022) - Pinto, A.L.; Cardoso, R.A.; Talemi, R.; Araújo, J.A.
Highlights: Crack initiation angle prediction in fretting fatigue tests under partial slip regime. Comparison between two methods to predict the crack initiation angle. Analysis of the influence of surface wear on crack nucleation angle. Comparison of numerical results with tests carried out for A7050-T7451 available in the literature. Abstract: This paper investigates two different methods to predict crack initiation direction in fretting problems subjected to partial slip conditions. One of them is based on the Critical Direction Method (CDM) combined with the Smith Watson and Topper (SWT) fatigue damage parameter. The other consists in simulating early crack propagation using a Linear Elastic Fracture Mechanics (LEFM) approach associated with the SWT parameter. In addition, this paper also investigates the influence of considering wear in the crack initiation direction estimates. For validation of the methods, experimental data from fretting tests conducted on an AA7050- T7451 alloy were used. Results have shown that the CDM-based model provides very accurate estimates, whereas the LEFM-based approach failed to properly reproduce experimental observations. Besides, it was also verified that the inclusion of wear has little effect on the estimates despite the method considered.